PEMBERIAN FASILITAS KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR WALIKOTA ADMINISTRASI TANGERANG - Akka Latifah Jusdienar; Sutarto Sutarto (Aliansi : Jurnal Manajemen dan Bisnis, 2022)
This study discusses how to extend the influence of work on employee morale. Note obtained through the survey by distributing questionnaries by 84 respondents in the Administrative Office of the Mayor Tangerang.Analysis of data obtained from the calculation that R=0.723. In other words, the relationship of working facilities (X) of the Employee Morale (Y) is very strong. The the calculation of coefficient of determination (KD) R square of 52,3% (from 0.53 x 100%). Mean magnitude of the effect of giving employment facilities (X) 52,3%) influenced other causes outside of this regression, for example, allowances, salaries, leadership style, and others. While a simple linear regression equation of Y = 22.784 + 0.502 X, of the value of the regression can be interpreted that if the provision of employment facilities (X) value is 0, then the employee morale value of 22.784. Regression coefficient of variable of variable working facilities (X) of 0.502, menaing that if one increase the value, then the volume of work facilities (Y) will increase an increase of 0.502.